Intermittent Fault Detection and Isolation System - Steadman, Bryan; Berghout, Floyd; Olsen, Nathan; Sorensen, Brent (2008 IEEE AUTOTESTCON, 2008)
Aging aircraft electronic boxes often pose a maintenance challenge in that often after malfunctioning during flight in the aircraft, they test good, or "No Fault Found" (NFF) during ground test. The reason many of these boxes behave in this manner is that they have intermittent faults, which are momentary opens in one or more circuits due to a cracked solder joint, corroded contact, sprung connector receptacle, or any number of other reasons. These NFF boxes often account for a substantial number of boxes processed through a maintenance facility, where no repair can be performed, because no problem can be detected. Conventional test equipment is designed to test the electronic box for nominal operation, and usually "averages out," and hence hides, any short term anomalous event. This paper describes a tester that was specifically designed to detect and isolate the intermittent circuits in an electronic box chassis. This new and innovative tester has been designated the Intermittent Fault Detection and Isolation System (IFDIS). The IFDIS very effectively compliments conventional testers. The IFDIS includes an environmental chamber and shake table to subject the box to simulated operational conditions, which greatly enhances the probability the intermittent circuit will manifest itself. The IFDIS also includes an intermittent fault detector which continuously and simultaneously monitors every electrical path in the chassis under test, while the box is exposed to a simulated operational environment. To determine the effectiveness of this new tester in detecting and isolating intermittent circuits, several dozen electronic boxes, identified by serial number, that had been to the repair facility and tested NFF multiple times were selected for IFDIS testing. One or more intermittent faults were detected, isolated and repaired in nearly every box. These boxes were then tested on the conventional tester and returned to service. We are currently monitoring their performance to determine their increased service life and reduced number of NFF incidents.